The Effects of Counseling and Drug Information Services by Pharmacist to Medication Adherence and Therapy Outcomes on Sciatica Patients at Dr. Suyoto Hospital, Jakarta - Farida Ariyani; Prih Sarnianto; Nurita Andayani (Jurnal Delima Harapan, 2021)
People suffered from sciatica, pain along the sciatic nerve, require therapy up to 4 months or longer to achieve controlled-pain. The main treatment for sciatica is physiotherapy; medication is only secondary therapy. This quasi-experimental study aimed to investigate the effects of counseling and drug information services (DIS) by pharmacist on medication adherence and duration of therapy. In the study conducted in March‒July 2018, 128 ambulatory sciatica patients newly diagnosed at Dr. Suyoto Hospital, Jakarta, were divided randomly into two groups, each of 64 patients. The intervention group was given counseling and DIS by clinical pharmacists (3 times with interval of 4 weeks) as well as brochures. Primary data on medication adherence were obtained prospectively through interviews using a validated questionnaire, before the intervention and 4 weeks after the last counseling and DIS by clinical pharmacists. Secondary data (up to 16 weeks), including pain scores, were obtained from medical records and the patient administrative data. The results showed that sociodemographic characteristics as well as distribution of initial adherence and initial pain levels of the two groups were not significantly different (Mann-Whitney test, p>0.05). After the last intervention, the proportion of patients with high-adherence in the intervention group (12.5%) was higher than in the control group (6.3%), as was the proportion of patient achieved controlled-pain (84.4% versus 76.6%). The results of survival analysis showed that the duration of treatment by which 50% of patients achieved controlled-pain (median survival) was significantly shorter in the intervention group (85 days) than in the control group (92 days), while the probability of achieving controlled-pain (hazard ratio) in the intervention group was 1.7 times of that in the control group. In conclusion, counseling and DIS by pharmacist can improve the effectiveness of sciatica treatment, although the main therapy for the nerve pain is not medication.